2011
DOI: 10.1086/658156
|View full text |Cite
|
Sign up to set email alerts
|

FrankiaAssemblages Associated withAlnus rubraandAlnus viridisAre Strongly Influenced by Host Species Identity

Abstract: This study examined the effect of host species identity on the structure of Alnus-associated Frankia bacterial assemblages in the Pacific Northwest, United States, using two approaches. First, Frankia in nodules were sampled from six stands of Alnus rubra or Alnus viridis. Second, a bioassay was conducted where A. rubra and A. viridis seedlings were grown in different soils collected from these two hosts. Frankia genotypes were characterized with nifH sequences and bacterial assemblages were compared using tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 48 publications
4
22
0
Order By: Relevance
“…Lipus and Kennedy (2011) demonstrated that the observed host-association pattern in USA Alnus forests was reproducible in reciprocal soil transplant experiments, and therefore appears to reflect a preference on the part of either the host or the microsymbiont for certain partners over others. Lipus and Kennedy (2011) demonstrated that the observed host-association pattern in USA Alnus forests was reproducible in reciprocal soil transplant experiments, and therefore appears to reflect a preference on the part of either the host or the microsymbiont for certain partners over others.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Lipus and Kennedy (2011) demonstrated that the observed host-association pattern in USA Alnus forests was reproducible in reciprocal soil transplant experiments, and therefore appears to reflect a preference on the part of either the host or the microsymbiont for certain partners over others. Lipus and Kennedy (2011) demonstrated that the observed host-association pattern in USA Alnus forests was reproducible in reciprocal soil transplant experiments, and therefore appears to reflect a preference on the part of either the host or the microsymbiont for certain partners over others.…”
Section: Discussionmentioning
confidence: 70%
“…In molecular diversity analyses of Frankia using nifH, the cutoff level of ≥97% sequence similarity results in taxonomic groups that reliably correlate to distinct, reproducible clades in phylogenetic analyses (Mirza et al 2009;Welsh et al 2009a;Kennedy et al 2010b;Lipus and Kennedy 2011). In addition, Lipus and Kennedy (2011) found evidence of host species-level associations among genotypes defined at this sequence similarity level.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations